Pengaruh Inkuiri Terbimbing Berbantu Jurnal Belajar Terhadap Aktivitas dan Hasil Belajar Kognitif - Wahyu Enggal Saputri; Darlen Sikumbang (Universitas Lampung, 2019)
This study aims to determine the effect of guided inquiry learning models aided with learning journal on activities and cognitive learning outcomes students of class X SMAN 2 Tulang Bawang Tengah in